2015
DOI: 10.1111/trf.13212
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood group with P‐selectin levels in Chinese Han healthy volunteers

Abstract: This study demonstrated an association between sP-selectin levels and ABO groups in a Chinese Han population, implicating its generalizability to other ethnic groups. This finding will improve the understanding of the mechanism of ABO blood group-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Similarly, Chen et al 46 also identified lower serum (but not platelet) P-selectin levels in Han Chinese, a population in which the A2 allele is not present. In MESA, HIS, EUR, and CHN participants all demonstrated a mean decrease of approximately 19% per A1 allele, in contrast to AFA, which only corresponded to a mean decrease of 9.5%.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Chen et al 46 also identified lower serum (but not platelet) P-selectin levels in Han Chinese, a population in which the A2 allele is not present. In MESA, HIS, EUR, and CHN participants all demonstrated a mean decrease of approximately 19% per A1 allele, in contrast to AFA, which only corresponded to a mean decrease of 9.5%.…”
Section: Discussionmentioning
confidence: 80%
“…ABO blood group constitute ABH-antigens which are complex carbohydrate molecules (glycoprotein and glycolipids) expressed on the extracellular surfaces of human cells and tissues, including red cell membrane, platelets, and vascular endothelial cell [1][2][3]. ABO blood group has been recognized as an essential system in clinical practice particularly in the field of transfusion and transplantation medicine [4]. Since its discovery, ABO group has been studied as etiological factors of many diseases [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence underpins CVDs to be linked with ABO blood group system [3,4,23,45] although the mechanism linking ABO blood group with CVD, particularly atherosclerosis, remains unclear. However, previous studies suggest that ABH antigen act as the principal agent for endothelial cell proliferation [3], as such plays a role in the disease process by a modulation in the vascular endothelial haemostasis [1,30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in AFA (P = 3.4E-06), we observed evidence of increased levels of RANTES and TGFβ-1, while HIS participants exhibited increased circulation of SLPI. These results, like others(Chen et al 2015; Kiechl et al 2011), seemingly contradict the hypothesis that sP-selectin may mediate the association between ABO blood type and atherosclerotic CVD, as increased sP-selectin has been shown to correlated with higher CVD risk(Ridker et al 2001). However, potential explanations have been proffered that accommodate this apparently paradoxical relationship(Kiechl et al 2011).…”
Section: Discussionmentioning
confidence: 60%
“…This glycoprotein is recognized to be directly modified by ABO glycosyltransferases, and Type O subjects have been shown to be at reduced risk for venous thromboembolism(Ohira et al 2007; Sode et al 2013; Wiggins et al 2009; Zakai et al 2014). Recent GWASs(Barbalic et al 2010; Chen et al 2015; Kiechl et al 2011) have also identified multiple ABO SNP associations with circulating levels of a number of markers of endothelial function, including sP-selectin and sICAM-1. Mechanistically, it has been suggested that ABO glycosyltransferases may regulate endothelial markers through cleavage or proteolysis, since ABO associations with sP-selectin have not been replicated for platelet-bound levels(Barbalic et al 2010).…”
Section: Discussionmentioning
confidence: 99%